Regulasi Wakaf Di Indonesia Dari Masa Orde Lama Sampai Era Reformasi Dalam Tinjauan Politik Hukum - Supriyadi, Supriyadi; Hadi, Sholihul (ZISWAF, 2019)
One important factor that contributed to the style and development of waqf in Indonesia was when the state participated in regulating waqf policies through a set of positive laws. In the process of formulating the policy, the vision and direction of waqf policy is largely determined by how the ruling regime sees the potential and organization of waqf, both in terms of its interests and the interests of Muslims in general. This study uses a qualitative method with a legal political approach. This study concludes that the politics of waqf law in Indonesia with a span of time from the era of independence to the era of reform. It is evident that each regulation in accordance with the era has differences according to the political conditions behind it. There are regulations that have greater political factors compared to other factors. The following are characteristics of waqf legal regulations in Indonesia, using categorization: dominant, somewhat weak and weak.